Hantavirus Nucleocapsid Protein Oligomerization - Alfadhli, Ayna (American Society for Microbiology, 2001)
Hantaviruses are enveloped, negative-strand RNA viruses which can be lethal to humans, causing either a hemorrhagic fever with renal syndrome or a hantaviral pulmonary syndrome. The viral genomes consist of three RNA segments: the L segment encodes the viral polymerase, the M segment encodes the viral surface glycoproteins G1 and G2, and the S segment encodes the nucleocapsid (N) protein. The N protein is a 420- to 430-residue, 50-kDa protein which appears to direct hantavirus assembly, although mechanisms of N protein oligomerization, RNA encapsidation, budding, and release are poorly understood. We have undertaken a biochemical and genetic analysis of N protein oligomerization. Bacterially expressed N proteins were found by gradient fractionation to associate not only as large multimers or aggregates but also as dimers or trimers. Chemical cross-linking of hantavirus particles yielded N protein cross-link products with molecular masses of 140 to 150 kDa, consistent with the size of an N trimer. We also employed a genetic, yeast two-hybrid method for monitoring N protein interactions. Analyses showed that the C-terminal half of the N protein plus the N-terminal 40 residues permitted association with a full-length N protein fusion. These N-terminal 40 residues of seven different hantavirus strains were predicted to form trimeric coiled coils. Our results suggest that coiled-coil motifs contribute to N protein trimerization and that nucleocapsid protein trimers are hantavirus particle assembly intermediates.